Major HIV vaccine candidates - Wojciech Zdziennicki; Patryk Zimnicki; Marta Lato; Konrad Iberszer; Maria Litwiniuk; Marcin Zaniuk; Kamil Hurkała; Dominika Antonik; Barbara Denys; Karolina Góra (Journal of Education, Health and Sport, 2023)
Introduction and objective: Human immunodeficiency virus (HIV) is a virus, which is responsible for an acquired immunodeficiency syndrome (AIDS). This pathogen is widespread worldwide causing a pandemic that has been going on for decades. Researches around the world are trying to end this situation and it seems that the greatest hope lies in finding an effective vaccine. It is important due to the fact that AIDS and its consequences are responsible even nowadays for death of many people infected around the world. The aim of this study was to provide the most important information about major HIV vaccine trials and efficacy of vaccine candidates.